An evolution of customer relationship management: a conceptual approach - Karunanithy, M.; Kajendra, K. (University of Jaffna, 2012)
This concept paper is a review of academic literature on Customer Relationship Management (CRM) and provides a comprehensive bibliography by seeing the development / usefulness of the definition about CRM. Around two hundred and fifty online databases were searched and out of which only fifty articles were found directly relevant to look into the development of CRM definition. Further, it provides a comprehensive idea developed on CRM from its populated period (1990s - 2010s). Identified articles were classified into three periods 1990s, 2000s and 2010s. These articles were reviewed independently to see the conceptual development of the phrase CRM. Papers and researches on CRM fall on various categories like, General, Marketing, Sales, Service and Support, IT and IS and further number of sub-categories. Here, it is considered only general category related papers which is very common among the research publications. It was found how the CRM phrase considered and importance was given from its populated period to 2010s.
Keywords: Customer Relations; Relationship Management; Research Work